Thyroid-Like Follicular Carcinoma of the Kidney in a Young Patient with History of Pediatric Acute Lymphoblastic Leukemia - William W. Wu; Julia T. Chu; Ali Nael; Sherif A. Rezk; Stephen G. Romansky; Lisa Shane (Hindawi Limited, 2014)
Thyroid-like follicular carcinoma of the kidney (TLFCK) is a rare histological variant of renal cell carcinoma not currently included in the World Health Organization classification of renal tumors. Only 24 previous cases of TLFCK have been reported to date. We report a case of TLFCK in a 19-year-old woman with history of pediatric acute lymphoblastic leukemia. This patient is the youngest with TLFCK to be reported to date and the first with history of lymphoblastic leukemia. The development of TLFCK in a young patient with history of lymphoblastic leukemia is interesting and suggests that genes involved in leukemogenesis may also be important for TLFCK pathogenesis. Recognition of TLFCK is important to distinguish it from other conditions that show thyroid-like features, as a misdiagnosis can result in adverse patient care.